1991
DOI: 10.1021/jm00112a032
|View full text |Cite
|
Sign up to set email alerts
|

GABA-uptake inhibitors: construction of a general pharmacophore model and successful prediction of a new representative

Abstract: A model for the pharmacophore of GABA-uptake inhibitors was established using published structure-activity data and molecular modeling. The model accounted for the activities of different classes of GABA-uptake inhibitors. Analogues of guvacine substituted at position 6 were synthesized in order to confirm the model. 6-(3,3-Di-phenylpropyl)guvacine (30f), which fit well with the pharmacophore, had an in vitro IC50 of 0.1 microM. This value is as good as those of the best GABA-uptake inhibitors known today.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 78 publications
(43 citation statements)
references
References 8 publications
0
42
0
1
Order By: Relevance
“…( B ) Top view of the pharmacophore, showing location of predicted hydrogen bonding interactions. ( C ) Structure of the GAT1 pharmacophore, adapted from N'goka et al . (1991) showing similarities in size and structure of the SGLT1 and GAT1 pharmacophores.…”
Section: Resultsmentioning
confidence: 99%
“…( B ) Top view of the pharmacophore, showing location of predicted hydrogen bonding interactions. ( C ) Structure of the GAT1 pharmacophore, adapted from N'goka et al . (1991) showing similarities in size and structure of the SGLT1 and GAT1 pharmacophores.…”
Section: Resultsmentioning
confidence: 99%
“…406 Recently Felluga et al 408 have reported the preparation of (R)-and (S)-2-(pyrrolidine-3-yl)acetic acid 1128 via a chemoenzymatic disymmetric hydrolysis of 3-nitromethylglutaric acid diethyl ester 1129 obtained from a Michael addition of nitromethane to diethyl glutaconate. Thus, desymmetrization of 1129 using porcine pancreatic lipase (PPL) gave monoester (R)-1130 in 98% ee and 79% yield, whereas treatment of 1129 with crude pig liver esterase (PLAP, pig liver acetone powder) produced monoester (S)-1130 in 99% ee and 82% yield.…”
Section: Synthesis Of N C N B Derivativesmentioning
confidence: 99%
“…Cyclic amino acids such as nipecotic acid and guvacine have been shown to inhibit GABA uptake. Moreover, it is active orally as an anticonvulsant in mice and rats with ED 50 Further developments demonstrated that the 4,4-diphenyl-3-butenyl moiety could be replaced by ether-type analogs [98,99] and that the attachment of a lipophilic 3,3-diphenylpropyl side-chain can take place at the carbon atom at the 6-position of the amino acid [100]. A considerable improvement has been the discovery by Yunger et al [96,97] of compound SKF 89976A, a N-(4,4-diphenyl-3-butenyl) substituted nipecotic acid.…”
Section: A To Increase Lipophilicitymentioning
confidence: 99%